2011
DOI: 10.1186/1471-2431-11-80
|View full text |Cite
|
Sign up to set email alerts
|

Duration of exclusive breastfeeding; validity of retrospective assessment at nine months of age

Abstract: BackgroundIn cross sectional, case control and retrospective cohort studies, duration of Exclusive Breastfeeding (EBF) usually depends on maternal recall. Retrospective data are often subjected to recall bias and could lead to a potential for exposure misclassification. The purpose of the present paper is to assess the validity of maternal recall of EBF duration during infancy, after cessation of EBF and to evaluate the two methods to collect retrospective data on EBF.MethodsA cohort study was carried out in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 8 publications
0
39
0
1
Order By: Relevance
“…Nevertheless, it has been shown that women successfully recall what happened during the process of giving birth and the following hours, even a long time later [28]. Agampodi and co-authors [29] argued that retrospective evaluation methods systematically overestimate the duration of breastfeeding, but our prevalence of 77% women breastfeeding exclusively for at least two months is similar to that of breastfeeding rates in Uppsala county during the same year (76,2%) [30]. A possible limitation of this study is that a question about intention to breastfeed was not directly posed, as we assumed that nearly all mothers had planned to breastfeed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been shown that women successfully recall what happened during the process of giving birth and the following hours, even a long time later [28]. Agampodi and co-authors [29] argued that retrospective evaluation methods systematically overestimate the duration of breastfeeding, but our prevalence of 77% women breastfeeding exclusively for at least two months is similar to that of breastfeeding rates in Uppsala county during the same year (76,2%) [30]. A possible limitation of this study is that a question about intention to breastfeed was not directly posed, as we assumed that nearly all mothers had planned to breastfeed.…”
Section: Discussionmentioning
confidence: 99%
“…Agampodi et al . reported similar findings at 9 months follow‐up, concluding that estimations of longer than observed EBF were likely a result of social desirability bias rather than recall bias. With regard to longer durations of recall, Promislow et al .…”
Section: Introductionmentioning
confidence: 62%
“…Bland et al (9) reported that 72% of mothers did not recall the period of exclusive breastfeeding (EBF) accurately 6-9 months post-delivery, with 57% overestimating the duration and 15% underestimating the duration. Agampodi et al (11) reported similar findings at 9 months follow-up, concluding that estimations of longer than observed EBF were likely a result of social desirability bias rather than recall bias. With regard to longer durations of recall, Promislow et al (7) assessed the validity of maternal recall of the duration of breastfeeding in elderly American women 34-50 years later, reporting a sensitivity for recall of having breastfed of 94%.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, accurate maternal recall of breastfeeding behavior positively correlates with shorter total recall period and seminal rather than nuanced events (e.g., infant age at complete weaning from breastfeeding more accurately recalled than age at first introduction of formula or solid foods), with a tendency for mothers to overestimate duration of exclusive breastfeeding (Burnham et al 2014, Agampodi et al 2011, Cupul-Uicab et al 2009, Barbosa et al 2012, Li et al 2005). Gillespie et al (2006) found that accuracy of recalled reasons for breastfeeding cessation varied 1–3.5 years after birth, with mastitis and return to work having greater recall validity than nipple trauma.…”
Section: Introductionmentioning
confidence: 99%